Investigation of Mixed MeOH:EtOH Ratio and Air Supply on MEA Performance in Direct Alcohol Fuel Cell (DAFC) - Yulianti, Dwi Hawa; Rohendi, Dedi; Majlan, Edy Herianto; Rachmat, Addy; Sya’baniah, Nyimas Febrika (Science and Technology Indonesia, 2025)
Methanol (MeOH) and ethanol (EtOH) are commonly used fuels in Direct Alcohol Fuel Cells (DAFC). The advantages of these two fuels are influenced by electrochemical reactions centered around the Membrane Electrode Assembly (MEA). In this study, Pt/C catalyst was used on the cathode and Pt-Ru/C on the anode, with catalyst loadings of 2, 4, 6, 8, and 10 mg/cm2. The anode and cathode were characterized using Cyclic Voltammetry (CV), while the conductivity properties were evaluated through Electrochemical Impedance Spectroscopy (EIS). The Open Circuit Voltage (OCV) of the MEA in a single DAFC cell reached 0.65 V, with the highest value observed at a MeOH:EtOH volume ratio of 70:30 at concentrations of 3 M for MeOH and 2 M for EtOH. In addition to oxidation at the anode, oxygen reduction plays a significant role in the MEA performance on the cathode side. The oxygen supply to the cathode increased the power density by 52.17% at the optimal blower voltage of 5 V.